Oxidative Esterification of Methacrolein to Methyl Methacrylate over Supported Gold Catalysts Prepared by Colloid Deposition. Issue 11 (2nd May 2017) - Li, Yuchao; Zheng, Yanxia; Wang, Lei; Fu, Zhongjun
Abstract: Esterification is one of the most pivotal organic transformations. Au catalysts were prepared by using a colloid deposition method with poly(vinyl alcohol) (PVA) as a protective agent. The catalyst was used for the oxidative esterification of methacrylate (MAL) to methyl methacrylate (MMA). Three pre‐treatments were used to remove the PVA, which is unfavorable for catalytic activity. It is found that the catalyst pre‐treated at 300 °C showed substantially improved activity owing to the lower PVA loading compared with catalysts treated with hot water washing and water reflux. Surprisingly, it is also found that the distribution and loading content of Au particles was closely related to the pH of the colloid solution. We demonstrate that the deposition process is controlled by the different charge of the support surface at different colloid solution pH. Further, the catalysts with similar size Au particles loaded on TiO2, SiO2, Al2 O3, CeO2, ZrO2, and ZnO were successfully prepared by controlling the colloid solution pH. The Au/ZnO catalyst presented the best performance, which may be a result of the strong basic surface sites that improved the formation of the intermediate and the strong interaction between Au and ZnO. This interaction caused an anchoring effect and changed the geometries of Au particles, which could enhance the stability of catalysts and promote the mobility of oxygen, respectively. Abstract : Au supported on ZnO, prepared by colloid deposition, gives a catalyst with good performance in the oxidative esterification of methacrolein to methyl methacrylate owing to the strong interaction between Au and ZnO.